THE EFFECT OF ABILITY, SOCIO DEMOGRAFI AND SELF EFFICACY ON ENTREPRENEURIAL INTENTION OF MENTAWAI ISLAND INDIGENOUS COMMUNITY - Novia Rahmawati; Yeasy Darmayanti; Daniati Puttri (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2022)
This research aims to test the effects of ability, socio demography, self efficacy on entrepreneurial intention of Mentawai Island indigenous community. This research is based on National Labor Force Survey (SAKERNAS) 2014-2016 which describe the number of unemployment, Statement by Regent of Mentawai Island about enterprises in Mentawai Island Regency were more dominated my migrants and foreign workers, Mentawai Island Regency was including in the 122nd underdeveloped regencies in 2015-2019, and development of entrepreneurs is considered as a strategic step in maintaining national economic problems. The number of samples in this study 90 respondents, obtained by using accidental sampling method. Hypothesis testing using multiple regression. Based on testing results in the first hypothesis, it is found out that ability influences significantly on entrepreneurial intention. The second hypothesis shows that socio demography influences significantly on entrepreneurial intension. And the third hypothesis also shows that self efficacy influences significantly on entrepreneurial intension